Gelatin-based sodium ion battery hard carbon negative electrode aqueous binder and preparation method thereof

Through the compounding technology of gelatin-based water-based adhesive, a three-dimensional network structure with high cross-link density is formed, which solves the problem of insufficient performance of hard carbon negative electrode adhesive of sodium ion battery, and achieves high peel strength and environmental protection effects.

CN119193058AActive Publication Date: 2024-12-27ZHEJIANG CASNOVO MATERIALS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411698045.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-27
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The adhesive performance of existing sodium ion batteries is insufficient, making it difficult to meet the demand for high peel strength.

Method used

Using gelatin-based water-based binder, gelatin is combined with acrylic monomers, acrylate monomers and polyol acrylates to form a three-dimensional network structure with high cross-linking density, combining azo or peroxygen initiators and pH adjuster, a binder with high cohesion and strength is prepared.

Benefits of technology

It significantly improves the peel strength of the binder to reach more than 8 N/m. It is suitable for use in sodium ion batteries, and is environmentally friendly and low-cost, and is suitable for applications in humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193058A_ABST
    Figure CN119193058A_ABST
Patent Text Reader

Abstract

The invention relates to the field of binders, in particular to a gelatin-based sodium ion battery hard carbon negative electrode water-based binder and a preparation method thereof. The gelatin-based aqueous binder for the hard carbon negative electrode of the sodium-ion battery is prepared from the following raw materials: gelatin, an acrylic monomer, an acrylate monomer, acrylic polyol ester, an initiator, a pH regulator and deionized water. Wherein the acrylic polyol ester comprises ethylene glycol diacrylate. The gelatin-based aqueous binder for the hard carbon negative electrode of the sodium-ion battery prepared by the preparation method disclosed by the invention is excellent in bonding performance, the peel strength can reach 8 N / m, and compared with the prior art, the gelatin-based aqueous binder has remarkable progress.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of binders, and in particular to a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder and a preparation method thereof. Background Art

[0002] Sodium is one of the most common elements on Earth, and its resource reserves are abundant, far higher than lithium. Therefore, sodium-ion batteries have significant advantages in raw material costs, which is conducive to reducing the overall manufacturing cost of batteries. Generally speaking, the cost of sodium-ion batteries can be reduced by 30% to 40% compared to the cost of lithium-ion batteries. In terms of safety, sodium-ion batteries have an ultra-wide operating temperature range. The normal operating temperature range is -40 ℃ to 800 ℃. It is not easy to have thermal runaway even at high temperatures. Compared with lithium-ion batteries, sodium-ion batteries have smaller short-circuit currents and instantaneous heat generation, and are less likely to cause fires or spontaneous combustion. In addition, although the production of sodium-ion batteries also involves raw materials such as heavy metals, compared with the impact of lithium-ion battery mining on the environment, sodium-ion batteries cause relatively less damage to the environment in terms of raw material acquisition.

[0003] The ionic radius of sodium ions is much larger than that of lithium ions, and conventional soft carbon graphite negative electrodes are not suitable. They need to be adjusted to amorphous carbon negative electrode materials. Amorphous carbon has the characteristics of large specific surface area, small particle size, and low tapping, and has higher adhesion and cohesion requirements for binders. Currently, for carbon negative electrode materials, commonly used binders include SBR or CMC. For example, patent document CN110854367B discloses a silicon-carbon negative electrode material slurry, and its preparation raw materials include SBR (styrene-butadiene latex binder) and CMC (sodium carboxymethyl cellulose); however, the bonding performance of SBR or CMC to carbon materials is limited, and the application effect is general.

[0004] Based on this, for those skilled in the art, how to prepare an adhesive with high peel strength suitable for the hard carbon negative electrode of sodium ion batteries is an industry technical problem that urgently needs to be solved. Summary of the invention

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder, the preparation raw materials of which include: gelatin, acrylic acid monomer, acrylate monomer, acrylic acid polyol ester, initiator, pH adjuster and deionized water.

[0006] As an implementable case, the mass ratio of gelatin, acrylic acid monomer, acrylate monomer, acrylic acid polyol ester and initiator is (10-15): (1-3): (5-8): (0.5-1): (0.1-0.6).

[0007] The gelatin molecular chain contains active groups such as amino, carboxyl and hydroxyl groups, which can react with acrylic monomers, acrylate monomers, and acrylic polyol esters to achieve the modification of gelatin. Through modification, the physical and chemical properties of gelatin-based binders can be adjusted to meet the needs of hard carbon negative electrodes for sodium ion batteries; in addition, through physical or chemical cross-linking modification, gels with interpenetrating network structures and double network structures can be formed. The product has reversible bonding properties. At the same time, gelatin can absorb 5 to 10 times its weight of water, which allows gelatin-based water-based binders to maintain good bonding properties in a humid environment, especially suitable for use in sodium ion batteries.

[0008] As an implementable example, the acrylic monomer includes: acrylic acid and / or methacrylic acid.

[0009] As an implementable case, the acrylic acid ester monomer includes: one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, isobutyl methacrylate, hydroxymethyl acrylate, hydroxyethyl acrylate, and hydroxypropyl acrylate.

[0010] Furthermore, the acrylic acid ester monomer includes one or more of hydroxymethyl acrylate, hydroxyethyl acrylate, and hydroxypropyl acrylate.

[0011] As an implementable case, the acrylic polyol ester includes one or more of ethylene glycol diacrylate, 1,4-butanediol diacrylate, pentaerythritol triacrylate, and bisphenol A propylene glycol dimethacrylate.

[0012] Furthermore, the acrylic acid polyol ester is ethylene glycol diacrylate.

[0013] Acrylic polyol esters can increase the cohesion and strength of the adhesive, which helps to improve the bonding performance of the product. An appropriate amount of acrylic acid monomer can improve the wettability and adhesion between the polymer and the carbon negative electrode material, thereby improving the bonding performance; the acrylic acid ester monomer contains a hydroxyl functional group, which can hydrogen bond with the polar groups on the surface of the carbon negative electrode material to enhance the bonding force between the polymer and the carbon negative electrode material; at the same time, the acrylic acid ester monomer can also be used as a cross-linking agent to increase the cross-linking density and water resistance of the polymer, which helps to improve the bonding performance. The inventors found that when acrylic acid monomer, acrylic acid ester monomer, and acrylic acid polyol ester are selected as raw materials, a cross-linking reaction occurs under the initiator to form a three-dimensional network structure with a high cross-linking density; the increase in cross-linking density helps to improve the cohesion and strength of the adhesive, thereby improving the bonding performance, and the peel strength of the product can reach more than 8 N / m.

[0014] As an implementable case, the initiator is an azo initiator and / or a peroxide initiator.

[0015] As an implementable case, the azo initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride, and azobisisobutylimidazoline hydrochloride.

[0016] As an implementable case, the peroxide initiator includes: one or more of benzoyl peroxide, lauroyl peroxide, di-tert-butyl peroxide, diisopropyl peroxide, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, tert-butyl perbenzoate, isopropyl hydroperoxide, tert-butyl hydroperoxide, ammonium persulfate, potassium persulfate, and sodium persulfate.

[0017] Furthermore, the initiator includes: one of ammonium persulfate, potassium persulfate, and sodium persulfate.

[0018] As an implementable case, the pH adjuster includes: one of sodium hydroxide aqueous solution, lithium hydroxide aqueous solution, sodium bicarbonate aqueous solution, and ammonia water.

[0019] As an implementable case, the mass concentration of the sodium hydroxide aqueous solution is 1-3 wt%.

[0020] The second aspect of the present invention provides a method for preparing a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder, comprising: S1. Mix deionized water, gelatin and acrylic acid monomer, add them into the reactor, heat to 35-40 °C, and stir for 30-60 min; S2, adding acrylate monomer, acrylic polyol ester and initiator, raising the temperature to 55-65 °C under an inert gas atmosphere, and then reacting for 5-10 hours; S3. After the reaction is completed, the system is cooled to room temperature, and a pH regulator is added to adjust the pH of the system to 6.5-7.5, and then diluted and stirred evenly to obtain the product.

[0021] Beneficial Effects (i) The present invention selects gelatin as the main raw material for preparing the adhesive, which can ensure that the product has certain adhesive properties, and gelatin has high stability at both high and low temperatures, and is particularly suitable for use in sodium ion batteries; in addition, gelatin adhesive not only does not have harmful effects on the human body, but can also be naturally degraded in the body, avoiding the environmental problems that may be caused by traditional adhesives.

[0022] (ii) The present invention selects acrylic acid monomer, acrylic acid ester monomer, and acrylic acid polyol ester as the raw materials of the adhesive. The three components can further improve the bonding performance of the product through cross-linking polymerization reaction, and the peel strength can reach more than 8 N / m.

[0023] (III) The present invention further defines the mass ratio of acrylic acid monomer, acrylic ester monomer, and acrylic polyol ester as (1-3): (5-8): (0.5-1), which can further improve the cohesion and strength of the adhesive and increase the service life.

[0024] (iv) The raw materials prepared in the present invention do not include organic solvents, the product system is relatively environmentally friendly, and the preparation process is relatively simple. The raw materials only need to be added in a certain order, stirred, and reacted. The source of the raw materials is relatively wide, the cost is relatively low, and the product has excellent performance, especially suitable for use in hard carbon negative electrodes of sodium ion batteries.

[0025] (V) Currently, the binders used in the hard carbon negative electrode of sodium ion batteries on the market are mostly prepared with SBR and CMC as raw materials, but the bonding performance is average. The present invention provides a new type of modified gelatin-based aqueous binder for the hard carbon negative electrode of sodium ion batteries, which has more excellent bonding performance and is a significant improvement compared with the existing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the peel strength of the aqueous binder for the gelatin-based sodium ion battery hard carbon negative electrode prepared in Example 1. DETAILED DESCRIPTION

[0027] Example 1 The first aspect of this example provides a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder, the preparation raw materials of which include, by weight: 100 g gelatin, 10 g acrylic acid, 50 g hydroxymethyl acrylate, 5 g ethylene glycol diacrylate, 1.65 g ammonium persulfate, 555 g sodium hydroxide aqueous solution with a mass concentration of 1 wt% and 2148 g deionized water.

[0028] The gelatin was purchased from Hengshui Hongcai Adhesive Co., Ltd.

[0029] The second aspect of this example provides a method for preparing a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder, comprising: S1. Mix 835 g of deionized water, 100 g of gelatin and 10 g of acrylic acid by weight, add to a reactor, heat to 35 °C, and stir for 45 min until the gelatin is completely dissolved; S2, add 50 g of hydroxymethyl acrylate, 5 g of ethylene glycol diacrylate and 1.65 g of ammonium persulfate, introduce 0.1 MPa of high-purity nitrogen, the ventilation time is 30 min, raise the temperature to 65 ° C under nitrogen atmosphere, and react for 8 h; S3. After the reaction is completed, the system is cooled to room temperature 25°C, and 555 g of a 1 wt% sodium hydroxide aqueous solution is added to adjust the pH of the system to 6.8. 1313 g of deionized water is added to dilute the product to a solid content of 6%, and stirred evenly to obtain the product.

[0030] The peel strength diagram of the aqueous binder for hard carbon negative electrode of gelatin-based sodium ion battery prepared in this example is shown in Figure 1 As shown; a total of 4 tests were conducted, and the average of the 4 tests was taken as the final result.

[0031] Example 2 The first aspect of this example provides a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder, the preparation raw materials of which include, by weight: 150 g gelatin, 30 g acrylic acid, 80 g hydroxymethyl acrylate, 10 g ethylene glycol diacrylate, 5.4 g ammonium persulfate, 833 g sodium hydroxide aqueous solution with a mass concentration of 2 wt% and 3760 g deionized water.

[0032] The gelatin was purchased from Hengshui Hongcai Adhesive Co., Ltd.

[0033] The second aspect of this example provides a method for preparing a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder, comprising: S1. According to weight, 730 g of deionized water, 150 g of gelatin and 30 g of acrylic acid were mixed, added into a reactor, heated to 35 °C, and stirred for 45 min until the gelatin was completely dissolved; S2, add 80 g of hydroxymethyl acrylate, 10 g of ethylene glycol diacrylate and 5.4 g of ammonium persulfate, introduce 0.1 MPa of high-purity nitrogen, the ventilation time is 30 min, raise the temperature to 55 ° C under nitrogen atmosphere, and react for 5 h; S3. After the reaction is completed, the system is cooled to room temperature 25°C, and 833 g of a 2 wt% sodium hydroxide aqueous solution is added to adjust the pH of the system to 7.0. 3030 g of deionized water is added to dilute the product to a solid content of 6%, and stirred evenly to obtain the product.

[0034] Example 3 The first aspect of this example provides a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder, the preparation raw materials of which include, by weight: 120 g gelatin, 20 g methacrylic acid, 65 g hydroxyethyl acrylate, 7 g ethylene glycol diacrylate, 2.12 g ammonium persulfate, 310 g sodium hydroxide aqueous solution with a mass concentration of 3 wt% and 3199 g deionized water.

[0035] The gelatin was purchased from Hengshui Hongcai Adhesive Co., Ltd.

[0036] The second aspect of this example provides a method for preparing a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder, comprising: S1. According to weight, 786 g of deionized water, 120 g of gelatin and 20 g of methacrylic acid were mixed, added into a reactor, heated to 35 °C, and stirred for 45 min until the gelatin was completely dissolved; S2, add 65 g of hydroxyethyl acrylate, 7 g of ethylene glycol diacrylate and 2.12 g of ammonium persulfate, introduce 0.1 MPa of high-purity nitrogen, the ventilation time is 30 min, raise the temperature to 60 ° C under nitrogen atmosphere, and react for 7 h; S3. After the reaction is completed, the system is cooled to room temperature 25°C, and 310 g of a 3 wt% sodium hydroxide aqueous solution is added to adjust the pH of the system to 6.9. 2413 g of deionized water is added to dilute the product to a solid content of 6%, and stirred evenly to obtain the product.

[0037] Example 4 The first aspect of this example provides a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder, the preparation raw materials of which include, by weight: 140 g gelatin, 15 g methacrylic acid, 70 g hydroxypropyl acrylate, 8 g ethylene glycol diacrylate, 2.33 g ammonium persulfate, 555 g sodium hydroxide aqueous solution with a mass concentration of 3 wt% and 2752 g deionized water.

[0038] The gelatin was purchased from Hengshui Hongcai Adhesive Co., Ltd.

[0039] The second aspect of this example provides a method for preparing a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder, comprising: S1. Mix 765 g of deionized water, 140 g of gelatin and 15 g of methacrylic acid by weight, add to a reactor, heat to 40 °C, and stir for 40 min until the gelatin is completely dissolved; S2, add 70 g of hydroxypropyl acrylate, 8 g of ethylene glycol diacrylate and 2.33 g of ammonium persulfate, introduce 0.1 MPa of high-purity nitrogen for 30 min, raise the temperature to 60 °C under nitrogen atmosphere, and react for 6 h; S3. After the reaction is completed, the system is cooled to room temperature 25°C, and 555 g of a 3 wt% sodium hydroxide aqueous solution is added to adjust the pH of the system to 6.8. 1987 g of deionized water is added to dilute the product to a solid content of 6%, and stirred evenly to obtain the product.

[0040] Comparative Example 1 This example provides a water-based binder, and the raw materials for preparation include, by weight, 29.47 g of SBR (50% solid content), 6.32 g of CMC, and 423.23 g of deionized water.

[0041] The preparation method of the water-based adhesive is as follows: 29.47 g of SBR, 6.32 g of CMC and 423.23 g of deionized water are mixed and stirred at room temperature of 25° C. to obtain the water-based adhesive.

[0042] The SBR and CMC were purchased from Guangzhou Songbai Chemical Co., Ltd.

[0043] Comparative Example 2 The specific implementation of this example is the same as that of Example 1, except that the raw materials for preparation in this example do not include ethylene glycol diacrylate.

[0044] Performance Testing 1. Peel strength 216 g of the binder of Example 1-4 was diluted with 243 g of deionized water, and 5 g of conductive agent and 500 g of hard carbon material were added. After the raw materials were completely infiltrated, they were dispersed at high speed for 4 h (rotation speed: linear speed 10 m / min), and then 72 g of deionized water was added to adjust the viscosity to 2500 mPa·s. The prepared slurry was coated on copper foil by a single-sided intermittent coater and baked, and then coated. The coated electrode was placed in an oven at 120°C and dried for 12 h. The dried electrode was rolled and cut, and measured according to the adhesive 180° peel strength test method in GB / T 2790-1995.

[0045] The specific test method of comparative example 1 is as follows: 5.26 g of conductive agent and 500 g of hard carbon material are added to 459.02 g of the binder of comparative example 1, and the raw materials are dispersed at high speed for 4 h after being completely infiltrated, and then 77 g of deionized water is added to adjust the viscosity to 2500 mPa·s, and the prepared slurry is coated on the copper foil through a single-sided intermittent coating machine and baked, and then coated (single-sided coating, surface density of 0.95 g / dm 2 ), the coated electrode was placed in a 120 ℃ oven to dry for 12 h, the dried electrode was rolled and cut, and the adhesive 180° peel strength test method in GB / T 2790-1995 was used for determination.

[0046] The model of the conductive agent is Super P, purchased from Shanghai Huiping New Energy Co., Ltd.; the model of the hard carbon material is BSHC-300, purchased from BTR New Materials Group Co., Ltd.

[0047] The test results are detailed in Figure 1 and Table 1.

[0048] Table 1

[0049] The peel strength of Example 1 is the average value of 4 tests, and the specific peel strength test results correspond to Table 2.

[0050] Table 2

[0051] Among them, serial number 1 represents Figure 1 The red line data in .

[0052] Number 2 represents Figure 1 The yellow line data in .

[0053] Number 3 represents Figure 1 The blue line data in .

[0054] Number 4 represents Figure 1 The green line data in .

[0055] It can be seen from the test results of the above Examples 1-4 that the peel strength of the adhesive prepared by the present invention is above 8 N / m, while the peel strength of the water-based adhesive prepared by compounding SBR and CMC in the prior art is significantly lower than that of the product provided by the present invention; in addition, it can be seen from Comparative Example 2 that not adding acrylic polyol ester also has a significant effect on the bonding performance of the product.

Claims

1. A gelatin-based sodium ion battery hard carbon negative electrode aqueous binder, characterized in that: The preparation raw materials include: gelatin, acrylic acid monomer, acrylic ester monomer, acrylic acid polyol ester, initiator, pH regulator and deionized water; The mass ratio of the gelatin, acrylic acid monomer, acrylic ester monomer, acrylic acid polyol ester and initiator is (10-15): (1-3): (5-8): (0.5-1): (0.1-0.6).

2. The gelatin-based sodium ion battery hard carbon negative electrode aqueous binder according to claim 1, characterized in that: The acrylic polyol ester includes one or more of ethylene glycol diacrylate, 1,4-butylene glycol diacrylate, pentaerythritol triacrylate, and bisphenol A propylene glycol dimethacrylate.

3. The gelatin-based sodium ion battery hard carbon negative electrode aqueous binder according to claim 1, characterized in that: The acrylic acid monomers include: acrylic acid and / or methacrylic acid.

4. The gelatin-based sodium ion battery hard carbon negative electrode aqueous binder according to claim 1, characterized in that: The acrylic acid ester monomers include: one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, isobutyl methacrylate, hydroxymethyl acrylate, hydroxyethyl acrylate and hydroxypropyl acrylate.

5. The gelatin-based sodium ion battery hard carbon negative electrode aqueous binder according to any one of claims 1 to 4, characterized in that: The initiator is an azo initiator and / or a peroxide initiator.

6. The gelatin-based sodium ion battery hard carbon negative electrode aqueous binder according to claim 5, characterized in that: The azo initiator includes one or more of azobisisobutyronitrile, azobisisoheptylnitrile, azobisisobutyramidine hydrochloride, and azobisisobutylimidazoline hydrochloride.

7. The gelatin-based sodium ion battery hard carbon negative electrode aqueous binder according to claim 5, characterized in that: The peroxide initiator includes one or more of benzoyl peroxide, lauroyl peroxide, di-tert-butyl peroxide, diisopropyl peroxide, methyl ethyl ketone peroxide, cyclohexanone peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, tert-butyl perbenzoate, cumene hydroperoxide, tert-butyl hydroperoxide, ammonium persulfate, potassium persulfate, and sodium persulfate.

8. The gelatin-based sodium ion battery hard carbon negative electrode aqueous binder according to claim 1, characterized in that: The pH regulator comprises: one of a sodium hydroxide aqueous solution, a lithium hydroxide aqueous solution, a sodium bicarbonate aqueous solution, and ammonia water.

9. The gelatin-based sodium ion battery hard carbon negative electrode aqueous binder according to claim 8, characterized in that: The mass concentration of the sodium hydroxide aqueous solution is 1-3 wt %.

10. A method for preparing a gelatin-based sodium ion battery hard carbon negative electrode aqueous binder according to any one of claims 1 to 9, characterized in that: include: S1. Mix deionized water, gelatin and acrylic acid monomer, add them into the reactor, heat to 35-40 °C, and stir for 30-60 min; S2, adding acrylate monomer, acrylic polyol ester and initiator, raising the temperature to 55-65 °C under an inert gas atmosphere, and then reacting for 5-10 hours; S3. After the reaction is completed, the system is cooled to room temperature, and a pH regulator is added to adjust the pH of the system to 6.5-7.5, and then diluted and stirred evenly to obtain the product.

Citation Information

Patent Citations

  • Lithium ion battery cathode aqueous adhesive as well as preparation method and cathode material thereof

    CN109777328A

  • Lithium ion battery negative electrode aqueous binder

    CN110982008A

  • Preparation method of water-based adhesive for stretching and debonding adhesive tape and stretching and debonding adhesive tape

    CN112760067A

  • High-purity acrylate adhesive, preparation method and application thereof, optical transparent film and preparation method thereof

    CN114517070A

  • Preparation method of homogeneous spherical hard carbon negative electrode material

    CN116395665A